Development of a Digital Problem Solving Skills Test Instrument: Model Rasch Analysis - Ida Yayu Nurul Hizqiyah; Ari Widodo; Siti Sriyati; Arifin Ahmad (Postgraduate, University of Mataram, 2023)
Biodiversity is one of the subjects in Biology class X. Learning about the concept of biodiversity should be done by analyzing real natural phenomena, especially regarding biodiversity that exists in daily life. The government through the Regulation of the Minister of National Education Number 23 of 2006 has set competency standards for high school graduates that correlate with 21st century skills. One of the 21st century competencies is problem solving skills. A total of 26 questions have been developed in measuring Digital Problem Solving skills on biodiversity material for high school students. The questions were declared valid and reliable based on the results of analysis using the Rasch model through the Winsteps program in a polytomous manner, including the criteria of item validity, construct validity, and content validity, reliability, and DIF. As an implication from this study, the questions that have been developed in this study can be used to measure Digital Problem Solving skills in Biology lessons in high school, especially in the subject of biodiversity